2018
DOI: 10.1002/ijc.31634
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption and risk of prostate cancer in the European Prospective Investigation into Cancer and Nutrition

Abstract: The epidemiological evidence regarding the association of coffee and tea consumption with prostate cancer risk is inconclusive, and few cohort studies have assessed these associations by disease stage and grade. We examined the associations of coffee (total, caffeinated and decaffeinated) and tea intake with prostate cancer risk in the European Prospective Investigation into Cancer and Nutrition. Among 142,196 men, 7,036 incident prostate cancer cases were diagnosed over 14 years of follow-up. Data on coffee a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…However, population-based study reported by Arab et al using data from the North Carolina-Louisiana Prostate Cancer Project showed no association between decaffeinated or caffeinated coffee (4 cups per day) and highly aggressive prostate cancer (OR 0.92, 95% CI 0.61-1.39) [69] (Table 2). Similarly, in a most recent European study, there was no evidence of association for risk of total prostate cancer or cancer by grade, grade or fatality, and consumption of total, decaffeinated, or caffeinated coffee [77]. The findings of these studies bring attention to potential anticancer effect of polyphenols in coffee in reducing progression and metastasis of prostate cancer.…”
Section: Coffeementioning
confidence: 75%
See 1 more Smart Citation
“…However, population-based study reported by Arab et al using data from the North Carolina-Louisiana Prostate Cancer Project showed no association between decaffeinated or caffeinated coffee (4 cups per day) and highly aggressive prostate cancer (OR 0.92, 95% CI 0.61-1.39) [69] (Table 2). Similarly, in a most recent European study, there was no evidence of association for risk of total prostate cancer or cancer by grade, grade or fatality, and consumption of total, decaffeinated, or caffeinated coffee [77]. The findings of these studies bring attention to potential anticancer effect of polyphenols in coffee in reducing progression and metastasis of prostate cancer.…”
Section: Coffeementioning
confidence: 75%
“…In both studies, there was no association with prostate cancer and coffee consumption. In a large cohort European Study reported by Sen and colleagues, no association was observed for tea consumption and risk of prostate cancer by grade, stage, or fatality [77].…”
Section: Green Teamentioning
confidence: 86%
“…Although Paller et al found a negative correlation between high intake of quercetin and prostate cancer risk is described, this effect is not statistically significant (Paller et al 2015). Moreover, these were not reproduced by other effects about the role of quercetin in prostate carcinogenesis (Geybels et al 2013;Sen et al 2019). Similarly, a case-control study conducted with Italian women and a prospective investigation among American women revealed a 37-43% reduction in ovarian cancer incidence, including serous tumors (Gates et al 2007).…”
Section: Epidemiological Evidences On the Role Of Dietary Flavonoids mentioning
confidence: 97%
“…The IARC experts also concluded a lack of association between coffee intake and prostate cancer risk [ 77 , 78 ]. More recent studies confirm this conclusion, with no evidence of association found regarding the consumption of total, caffeinated, or decaffeinated coffee and risk of total prostate cancer or cancer by stage, grade, or fatality in the large European Prospective Investigation into Cancer and Nutrition (EPIC) cohort [ 133 , 134 ].…”
Section: Impact Of Coffee On Cancer Risk In Humansmentioning
confidence: 99%